Influence of Working Length on Post-operative Pain after Single or Two-Visit Endodontic Treatment: A Randomised Clinical Trial - Cardoso Tarallo, Alessandra Manchini [UNESP]; Matatos, Felipe de Souza [UNESP]; Bresciani, Eduardo [UNESP]; Paranhos, Luiz Renato; Ribeiro Camargo, Carlos Henrique [UNESP] (Premchand Shantidevi Research Foundation, 2018)
Introduction: Microorganisms in the cemental canal can lead to the development of periapical lesions and its mechanical removal by means of overinstrumentation may be more favourable for the success of endodontic treatment. However, instrumentation of the apical foramen remains a controversial issue because it can be a traumatic procedure to the periapical tissues. Aim: Considering that post-operative pain is an essential feature of symptomatic periradicular inflammation, this clinical trial evaluated the influence of two different foraminal working lengths on post-operative pain and mechanical allodynia after endodontic treatment completed in single-visit or two-visit. Materials and Methods: Forty eight adult patients indicated for primary endodontic treatment of tooth with asymptomatic apical periodontitis were randomly assigned to 4 groups (n = 12): SV0 - single-visit and instrumentation up to the apical foramen; SV+1 - single-visit and instrumentation 1 mm beyond the apical foramen; TV0 - two-visit and instrumentation up to the apical foramen; TV+1 - two-visit and instrumentation 1 mm beyond the apical foramen. All participants received a visual analog scale to record their assessment of pain at 3 hours to 7 days and data were analysed statistically by Kruskal-Wallis test (alpha = 5%). For mechanical allodynia evaluation, bite force measurement was performed using a digital gnathodynamometer just before and 7 days after treatment and data were analysed statistically by ANOVA and Tukey's test (alpha = 5%). Results: No statistically significant difference was found among the 4 groups in relation to post-operative pain at all time points assessed. Bite force values were significantly higher 7 days after endodontic treatment, indicating that there was a significant reduction of mechanical pain in all groups, with no significant difference among them. Conclusion: All groups exhibited the same rate of post-operative pain at the time points assessed and endodontic treatment effectively increased the mechanical pain thresholds.
Keywords: Endodontics; Foraminal enlargement; Hyperalgesia